Nutritional Quality of Meat Analogues: Results From the Food Labelling of Italian Products (FLIP) Project - Cutroneo, Sara; Angelino, Donato; Tedeschi, Tullia; Pellegrini, Nicoletta; Martini, Daniela; , SINU Young Working Group; Dall'Asta, Margherita; Russo, Marika Dello; Nucci, Daniele; Moccia, Stefania; Paolella, Gaetana; Pignone, Veronica; et al. (Frontiers in Nutrition, 2022)
Nowadays, the interest in meat substitutes is increasing, and consumers perceive their nutritional quality better than that of the animal products they intend to resemble. Therefore, this work aimed to investigate the overall nutritional quality of these new products. Regulated information (Regulation (EU) 1169/2011), the presence/absence of nutrition or health claim and organic declarations, the gluten-free indication, and the number of ingredients were collected from the food labels of 269 commercial meat analogues currently sold on the Italian market. Nutritional information of reference animal meat products was used to compare the nutrition profile. As an indicator of the nutritional quality, the Nutri-Score of meat analogues and counterparts was also determined. Plant-based steaks showed significantly higher protein, lower energy, fats and salt contents, and better Nutri-Scores than the other analogues. All the meat analogues showed a higher fibre content than meat products, while plant-based burgers and meatballs had lower protein contents than meat counterparts. Ready-sliced meat analogues showed a lower salt content than cured meats. Overall, all these plant-based products showed a longer list of ingredients than animal meat products. Results from this survey highlighted that plant-based steaks, cutlets, and cured meats have some favourable nutritional aspects compared to animal-based products. However, they cannot be considered a “tout-court” alternative to meat products from a nutritional point of view.